Less Is More Intense - Magnus Larsson (Oz, 2011)
A few months ago, I stood in front of one of the world’s most augmented buildings, or, at least, one of the buildings that has housed the most augmentation throughout its life. The Vehicle Assembly Building (VAB) at the John F. Kennedy Space Center on Merritt Island, Florida, is a hobbyist’s back-garden shed transposed to the science fiction-tinged, hyper-professional mega-scale at which NASA operates.